Liquefaction of pistachio nut shells - (:unkn) unknown (My University, 2008)
Pistachio nut shells are generally evaluated by combustion to generate heat is not efficient due to their low heating value. However, promising results may be obtained on their conversion to liquid and gaseous products to be used as energy sources and/or raw materials for organic synthesis. The influence of some process variables (temperature, initial cold hydrogen pressure, and tetralin to solvent mixture ratio) on the liquefaction yields of pistachio nut shells were studied at 325°-375°C and 10-30 atm. The effects of these parameters on oil+gas, asphaltene and pre-asphaltene yields, and total conversion as dependent variables were evaluated. Temperature and the tetralin to solvent mixture ratio were the main controlling variables on liquefaction yields. Cold hydrogen pressure was not effective on liquefaction yields. The optimal solution was obtained at 363°C, 13.1 atm cold hydrogen pressure, and 1:1 tetralin/solvent mixture ratio, with a 72.66% total conversion and yielded 53.72% oil+gas, 11.81% asphaltene, and 7.14% pre-asphaltene. Based on the calorific values, the analyzed oil product and residue samples were more valuable than pistachio nut shells as energy sources. This is an abstract of a paper presented at the 18th International Congress of Chemical and Process Engineering (Prague, Czech Republic 8/24-28/2008).